The Etiology of Neonatal Intensive Care Unit Death in Extremely Low Birth Weight Infants: A Multicenter Survey in China - Zhou, Jianguo; Ba, Yin; Du, Yang; Lin, Sam Bill; Chen, Chao; on behalf of the Chinese Collaborative Study Group for Etiologies of NICU Deaths (American Journal of Perinatology, 2020)
Objective The aim of this study is to identify causes of neonatal intensive care unit (NICU) death in extremely low birth weight (ELBW) infants less than 1,000 g admitted in Chinese tertiary NICUs.Study design We retrospectively collected data on 607 ELBW infants from 39 level III NICUs from July 2016 to June 2019. The primary causes of death were compared among different gestation age, postnatal age groups, and areas with variable economic status.Results Among all 607 ELBW NICU deaths, 47.1% were multiple gestation with high rate of in vitro fertilization (IVF) (43.3%); 53.4 and 34.1% received any or full course of antenatal corticosteroid (ACS). The most common causes of ELBW NICU death were respiratory distress syndrome-related neonatal respiratory failure (RDS-NRF, 43.5%), severe infection (19.1%), necrotizing enterocolitis or bowel perforation (9.4%), severe central nervous system injury (8.4%), and bronchopulmonary dysplasia-related respiratory failure (BPD-NRF, 7.7%). Causes of ELBW NICU death varied across postnatal age groups. RDS-NRF was the leading cause of early neonatal death, while severe infection in late neonatal death and BPD in postneonatal EBLW NICU death. RDS-NRF, severe brain injury, and asphyxia were most likely to die at early neonatal age (median age [interquartile range], 2 [0–5], 6 [3–9], and 3 [1–6] days, respectively) while severe infection and necrotizing enterocolitis (NEC) at late neonatal age, BPD-NRF at postneonatal age.Conclusion In Chinese tertiary NICUs, the major causes of death in extremely low birth weight infants were RDS, infection, NEC, brain injury and BPD, and they varied with postnatal age. Developing specific prevention strategies for identified causes of death in ELBW NICU may potentially improve ELBW survival.
Keywords: neonatal intensive care unit death; extremely low birth weight infants; respiratory distress syndrome; necrotizing enterocolitis; bronchopulmonary dysplasia